Implementasi Model Problem Based Learning pada Pembelajaran Matematika - Ibnu Imam Al Ayyubi; Nendi Rohaendi; Risman Herdiansyah; Tesha Puspita (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2024)
This research aims to see whether there are significant differences or interactions in mathematics learning outcomes with the problem-based learning model carried out at the elementary school level by correlating them with the student's gender. This research was carried out at SDN 074 Ayudia, Bandung City using a quantitative approach. This research uses a survey method and Two Ways ANOVA test analysis to see the relationship between student mathematics learning outcomes, student class, and student gender. The population of this study were students at SDN 074 Ayudia with a sample of 82 students consisting of 27 students in class VI A, 27 students in class VI B, and 28 students in class VI C. In this study, it was found that there were significant differences between student learning outcomes. class VI A, B, and C were analyzed based on male and female gender. However, from these differences, there was no significant interaction with student learning outcomes. Apart from that, it was found that there were no significant differences between classes VI A and VI B, whereas in classes VI A and VI C and VI B and VI C there were significant differences in the treatment of mathematics learning using the problem-based learning model. Thus, for further research, it is hoped that classes in mathematics learning can be prepared with each class providing a different learning model that is linked to students' initial mathematical abilities to see the differences and interactions in their learning outcomes.